Responses to larval herbivory in the phenylpropanoid pathway of Ulmus minor are boosted by prior insect egg deposition - Schott Johanna; Fuchs Benjamin; Böttcher Christoph; Hilker Monika (Springer, 2022)
Plant responses to insect eggs can result in intensified defences against hatching larvae. In annual plants, this eggmediated effect is known to be associated with changes in leaf phenylpropanoid levels. However, little is known about how trees—long-living, perennial plants—improve their egg-mediated, anti-herbivore defences. The role of phytohormones and the phenylpropanoid pathway in egg-primed anti-herbivore defences of a tree species has until now been left unexplored. Using targeted and untargeted metabolome analyses we studied how the phenylpropanoid pathway of Ulmus minor responds to egg-laying by the elm leaf beetle and subsequent larval feeding. We found that when compared to untreated leaves, kaempferol and quercetin concentrations increased in feeding-damaged leaves with prior egg deposition, but not in feeding damaged leaves without eggs. PCR analyses revealed that prior insect egg deposition intensified feeding-induced expression of phenylalanine ammonia lyase (PAL), encoding the gateway enzyme of the phenylpropanoid pathway. Salicylic acid (SA) concentrations were higher in egg-treated, feeding-damaged leaves than in egg-free, feeding-damaged leaves, but SA levels did not increase in response to egg deposition alone—in contrast to observations made of Arabidopsis thaliana. Our results indicate that prior egg deposition induces a SA-mediated response in elms to feeding damage. Furthermore, egg deposition boosts phenylpropanoid biosynthesis in subsequently feeding-damaged leaves by enhanced PAL expression, which results in the accumulation of phenylpropanoid derivatives. As such, the elm tree shows similar, yet distinct, responses to insect eggs and larval feeding as the annual model plant A. thaliana.